Solvent-Controlled Divergent Syntheses of Polycyclic N-Fused Heteroaromatics - Dagar, Anuradha; Joshi, Dirgha Raj; Kim, Ikyon (Synthesis, 2020)
Due to a growing interest in aza-fused polyaromatic systems among various sciences, enormous attention has been continuously paid to design and synthesize novel chemotypes of N-fused heterocycles. During the course of continued efforts in this line, it was found that divergent access to new polycyclic N-fused heteroaromatics was enabled by choice of reaction solvent. Described herein are solvent-controlled selective approaches to three novel N-fused azacycles, benzo-[d]imidazole-pyrrolo[1,2-a]pyrazine hybrids, under mild conditions. The plausible reaction mechanism for each class of compound is suggested as well.
Keywords: polycyclic heteroaromatics; hybrid structure; benzo[d]-imidazole; pyrrolo[1,2-a]pyrazine; chemical space; diversity-oriented synthesis; atom-economy; fluorescence